Prevalence of cognitive impairment and its associated factors in type 2 diabetes mellitus patients with hypertension in Hunan, China: a cross-sectional study - Liu, Hongying; Feng, Ziling; Zhang, Wenyan; Liu, Yamin; Xiong, Ni; Chen, Wenhang; Yang, Jianzhou; Wu, Xin Yin; Shi, Zeya; Dai, Wenjie (Frontiers in Psychiatry, 2024)
BackgroundIndividuals with both type 2 diabetes mellitus (T2DM) and hypertension have an increased risk of cognitive impairment (CI) compared to those with either T2DM or hypertension. Therefore, this study aims to identify the prevalence of CI and its associated factors in T2DM patients with hypertension in Hunan, China.MethodsThis cross-sectional study included T2DM patients with hypertension admitted to the Department of Endocrinology of Yuanjiang People’s Hospital in Hunan Province from July 2022 to February 2023. Data on sociodemographic, lifestyle, disease-related characteristics, and cognitive function were collected through face-to-face interviews. Cognitive function was assessed using the Mini-Mental State Examination. Backward stepwise multivariable logistic regression analysis was used to identify factors associated with CI. The predictive power was examined using the receiver operating characteristic (ROC) curve.ResultsA total of 475 participants were included. The prevalence of CI was 38.9% (95% confidence interval [95% CI]: 34.5%–43.3%). Multivariable logistic regression analysis showed that advanced age (odds ratio [OR]=3.21, 95% CI: 1.74–5.93), elementary school or below (OR=3.51, 95% CI: 1.19–10.31), per capita monthly household income ≤2000 RMB (OR=5.29, 95% CI: 2.66–10.51), not current reading books or newspapers (OR=4.48, 95% CI: 1.26–15.99), not current playing cards or mahjong (OR=3.52, 95% CI: 1.91–6.47), current average time of physical activity ≤30 minutes per day (OR=8.66, 95% CI: 4.65–16.12), diabetic nephropathy (OR=1.95, 95% CI: 1.05–3.61) and stroke (OR=7.41, 95% CI: 3.41–16.11) were associated with a higher risk of CI in T2DM patients with hypertension. The area under the ROC curve of this model was 0.925 (95% CI: 0.902–0.949).ConclusionsThe prevalence of CI was high in T2DM patients with hypertension in Hunan, China. Age, educational level, household income, current reading books or newspapers status, current playing cards or mahjong status, current average time of physical activity per day, diabetic nephropathy, and stroke were associated with CI in T2DM patients with hypertension.